Chapter 5 Financial relations in the Italian regional system - Valdesalici, Alice (Taylor & Francis, 2021)
The chapter concentrates on the impact of the 2001 constitutional reform on the 'financial constitution' and its later implementation in 2009 (by means of law 42/2009 and the following enactment decrees), paying attention to the subnational level of government (i.e. the regions). After a preliminary introduction on the system in force prior to 2001 section I), the constitutional principles of the 'financial constitution' are investigated (section II). This is done going through the landmark judgments of the Constitutional Court in their evolution over time. An overview of the implementing regulations (law 42/2009 and the related enactment decrees) is also provided (section III). The impact of the economic crisis on the 'regional system of financing to-be' is analysed (section IV), having particular regard to the case-law of the Constitutional Court, prior and after the constitutional entrenchment of the principle of balanced budget in 2012. The asymmetrical design of Italian regionalism is particularly evident when it comes to financial relations and related agreements. Each special region has a different system of powers and of financing based on bilateral negotiations with the national government. Section V is devoted to a brief overview of the financial regime of special regions, highlighting the impact exerted by the reform and the crisis. To conclude, par. 6 investigates the way forward of fiscal federalism in Italy, in order to identify the possible solutions out of the current deadlock the Italian regional system.